Implementasi Peraturan Daerah Nomor 3 Tahun 2017 Tentang Pemberdayaan Dan Perlindungan Perempuan Dari Tindak Kekerasan - Nur Halimah Al Fauziah; Aenal Fuad Adam (PAPSEL RESEARCH AND CONSULTANT, 2025)
The purpose of the study was to determine the implementation of Regional Regulation Number 3 of 2017 Concerning the Empowerment and Protection of Women carried out by the Women's Empowerment Service of Merauke Regency in the Protection of Women in the household realm recognized by the state from acts of violence in Merauke City. According to Van Metter and Van Horn, the theory used is the Policy Implementation theory. This study uses a qualitative approach and a case study research type. Data collection techniques are interviews, observation, and documentation—data analysis techniques include data reduction, data presentation, and conclusion. The number of informants is ten informants. Based on the results of this study, it can be concluded that the inter-organizational communication indicator could be more optimal. In the aspect of communication within the organization itself, there has been no socialization program on regional regulations for human resources and aspects of prevention efforts because they have yet to utilize social media, which is currently trending in disseminating information. Policy Resource Indicators, human resources, and facilities already exist but still have obstacles, namely internal obstacles, there are no special officers who manage the gender data system, and external barriers, namely the personnel of each victim themselves because of their marital status, which is not yet legal and economic dependence on the perpetrator who is the backbone of the family and physical facilities, there are no safe houses or shelters.